Pengaruh Campuran Lempung Dan Eceng Gondok Sebagai Adsorben Untuk Penyisihan Besi (Fe), Mangan (Mn) Dan Warna Pada Air Gambut - Putri Elisa S; Aryo Sasmita; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Clay and water hyacinth are natural resource which is a lot. Water hyacinth in huge amount can disturb the water ecosystem, whereas it can be use as adsorbent to remove polutant, especially metal. Both of them have a good removal efficiency for polutant that requiring another research to know the leverage of interfence of clay and eichornia crossipes against polutant. Research using adsorbtion method by varying the mass ratio of the interference that is 1; 1,5; 2 and 2,5 gr. The result showed that interfence adsorbent with water hyacinth 1 gr and clay 2,5 gr of mass ratio is the best interfence to remove mangan (Mn), organic substance and color in amount of 82,61%, 58,89% and 85,75%, while the additional of 1 gr of water hyacinth can remove 88,98% of iron (Fe). The interfence adsorbent is not effective to remove organic substance and color in peat water because the concentration is still passing the quality standard set by Permenkes Number 492/2010.Keywords : Clay, water hyacinth and adsorbtion